The The Effect of Reciprocal Teaching and Motivation on Students’ Reading Comprehension Text at The Second Grade STKIP Tapanuli Selatan Padangsidimpuan - Nina Nurbaidah (Jurnal Education and Development, 2016)
Vol. 3 No. 1 Nopember 2016 This study was conducted to find out the effect of reciprocal teaching and motivation on students’ reading comprehension. The design of this research was a quasi experimental research with factorial design 2x2. The population of this research was the second grade students of STKIP Tapanuli Selatan Padangsidimpuan academic year 2015/2016 which consisted of three classes (96 students). The sample was chosen by using cluster random sampling strategy. The sample was IVA as the experimental class (32 students) and IVB as the control class (32 students). The instruments used for collecting the data in this research were reading motivation questionnaire and reading comprehension test. In analyzing the data, t-test and two way anova analysis were used. The result of this research indicates that: first, reciprocal teaching strategy produce significant effect toward students’ reading comprehension compared to conventional strategy. Second, the students’ reading comprehension with high motivation taught by reciprocal teaching strategy produces higher result than those who taught by using conventional teaching. Third, students’ reading comprehension with low motivation taught by reciprocal teaching strategy produces higher result than those who taught by using conventional teaching. Fourth, there is no interaction between the strategies used (reciprocal teaching strategy and conventional teaching strategy) and students’ reading motivation on students’ reading comprehension. Based on the finding, it is concluded that reciprocal teaching strategy gives significant effect on students’ reading comprehension and this strategy is very beneficial as investment to enhance reading motivation and affect students’ reading comprehension. Key Words: Reciprocal Teaching, Motivation, Reading Comprehension